Effects of mentoring and field study instructional strategies on students’ learning outcomes in climate change concepts in social studies in Lagos state (2016)
Climate change is an environmental challenge that needs urgent attention. It is for this reason it is taught in Social Studies at the Junior Secondary School level to impart environmental knowledge. Literature was largely descriptive survey on awareness, perception and attitude to climate change without considering instructional interventions. This study determined the effects of mentoring and field study instructional strategies on students’ learning outcomes in climate change concepts in Social Studies in Lagos State. It also examined the moderating effects of gender and school location. The Constructivist, Eco-biological system and Social-learning theories provided the framework. The study adopted pretest-posttest, control group, quasi-experimental design of 3x2x2 matrix. Six public Junior Secondary Schools (JSS) were purposively selected from Lagos Island and Lagos Mainland Education Districts, Lagos State. The justification for the choice of these districts is that Lagos Island schools are mostly bounded by creeks and rivers while Lagos Mainland schools are mainly upland. Six intact JSS classes (one per school) comprising 284 students (143 males and 141 females) were randomly assigned to Mentoring (100), Field study (96) and Conventional (88) strategies. Treatment lasted ten weeks. Instruments used were: Students’ Knowledge of climate change test (r=0.77); Students’ attitude to climate change questionnaire (r=0.96); Climate change reduction practice questionnaire (r=0.96), and Instructional Guides for Mentoring, Field study and Conventional Strategies. Data were analysed using Analysis of Covariance and Scheffe post-hoc test at 0.05 level of significance. Treatment had significant main effects on students’ knowledge of climate change concepts (F(2,271) =11.86, η2=0.08), attitude (F(2,271)=8.74; η2= 0.06), and reduction practices (F(2,271) = 12.72; η2= 0.09). Students in mentoring strategy group had highest mean knowledge score (x ̅=12.35), followed by their counterparts in field study (x ̅=11.88) and control group (x ̅=10.67). For students’ attitude to climate change concepts, (F(2,271)= 8.74; η2= 0.06), control group had highest score (x ̅=42.36), followed by those in field study strategy group (x ̅= 41.67) and mentoring strategy group (x ̅ = 40.08). Field study strategy( x ̅ = 45.57) and mentoring strategy group (x ̅=45.00) scored higher than the control group (x ̅=40.86) in climate change reduction practices.There was a significant interaction effect of treatment and school location on knowledge of climate change concepts (F(2,271) = 3.45; η2= 0.03), and attitude scores(F(2,271) = 4.37;η2= 0.03) of students from Lagos Island and Mainland schools. There was no significant interaction effect of treatment and school location on the climate change reduction practices scores of students from Lagos Island and Mainland schools.The two-way interaction as well as the three-way interaction effects were not significant. Mentoring and field study instructional strategies were effective in enhancing students’ learning outcomes in climate change concepts in Social Studies in Lagos state, Nigeria. Teachers should adopt these strategies for effective teaching and learning of climate change concepts in Social Studies.